POTENTIAL ANALYSIS OF AGRICULTURAL SUBSECTORS IN PROBOLINGGO REGENCY, EAST JAVA - Kusuma, Mani’atul Fitan; Widayanti, Sri; Wijayati, Prasmita Dian (Yayasan Education and Social Center, 2024)
National development efforts can be strengthened by understanding and identifying the potential economic sectors in the region. An important part of the economic sector is the agricultural sector, whose performance depends on various subsectors, including food crops, plantations, horticulture, animal husbandry, agricultural services, forestry and logging, and fisheries. The purpose of this study is to analyze the leading agricultural subsectors and the potential of agricultural subsectors in the future in Probolinggo Regency and identify the description of the pattern and economic structure of the agricultural subsector in Probolinggo Regency. The data needed is GRDP data at constant prices of Probolinggo Regency and East Java Province in 2011-2022. The methods used in this analysis are Location Quotient (LQ), Dynamic Location Quotioent (DLQ), and Klassen's typology. The results found that during the 2011-2022 period, several sectors such as food crops, plantations, horticulture, livestock, agricultural services, forestry, and fisheries in Probolinggo Regency were basic, characterized by LQ values > 1. DLQ analysis shows that the food crops and plantations sectors are expected to tend towards non-base sectors, while the horticulture, livestock, agricultural services, forestry, and fisheries sectors are expected to tend to remain in the base sector. Klassen typology analysis illustrates that food crops and plantations are in quadrant III, indicating progress but slow growth, while horticulture, livestock, agricultural services, forestry, and fisheries are in quadrant I, indicating rapid growth and progress